Under pressure ; Cool and light [videorecording] - Lazaro, Cheche (The Probe Team., 1991)
Interview with the gold hundred and PCGG officials on the burried treasures at Bastion de San Lorenzo, Fort Santiago. Present the sentimental music of Kalapana and their singing career and Kenny Rankin.